- Ordering Rounding and Order of Operations
- Home
- Introduction to Inequalities
- Comparing a Numerical Expression With a Number
- Ordering Large Numbers
- Rounding to Tens or Hundreds
- Rounding to Hundreds or Thousands
- Rounding to Thousands, Ten Thousand, or Hundred Thousand
- Estimating a Sum of Whole Numbers
- Estimating a Difference of Whole Numbers
- Estimating a Product of Whole Numbers
- Estimating a Quotient of Whole Numbers
- Writing Expressions Using Exponents
- Introduction to Exponents
- Power of 10: Positive Exponent
- Power of 10: Negative Exponent
- Introduction to Parentheses
- Comparing Numerical Expressions With Parentheses
- Introduction to Order of Operations
- Order of Operations With Whole Numbers
- Order of Operations With Whole Numbers and Grouping Symbols
- Order of Operations With Whole Numbers and Exponents: Basic

- Selected Reading
- UPSC IAS Exams Notes
- Developer's Best Practices
- Questions and Answers
- Effective Resume Writing
- HR Interview Questions
- Computer Glossary
- Who is Who

# Order of Operations With Whole Numbers Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to **Order of Operations With Whole Numbers**. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using **Show Answer** button. You can use **Next Quiz** button to check new set of questions in the quiz.

### Answer : D

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right

,p>18 ÷ 3 + 3 × 3 – 8 = 6 + 9 – 8**Step 2:**

We do all addition and subtraction from left to right

6 + 9 – 8 = 15 – 8 = 7

**Step 3:**

So 18 ÷ 3 + 3 × 3 – 8 = 7

### Answer : B

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

28 ÷ 7 + 6 × 5 – 14 = 4 + 30 – 14

**Step 2:**

We do all addition and subtraction from left to right

4 + 30 – 14 = 34 – 14 = 20

**Step 3:**

So 28 ÷ 7 + 6 × 5 – 14 = 20

### Answer : A

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

,p>17 × 3 – 42 ÷ 14 – 18 = 51 – 3 – 18**Step 2:**

We do all addition and subtraction from left to right

51 – 3 – 18 = 51 – 21 = 30

**Step 3:**

So 17 × 3 – 42 ÷ 14 – 18 = 30

### Answer : C

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

8 – 12 ÷ 4 + 5 × 3 = 8 – 3 + 15

**Step 2:**

We do all addition and subtraction from left to right

8 – 3 + 15 = 5 + 15 = 20

**Step 3:**

So 8 – 12 ÷ 4 + 5 × 3 = 20

### Answer : B

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

20 – 18 ÷ 6 + 9 × 2 = 20 – 3 + 18

**Step 2:**

We do all addition and subtraction from left to right

20 – 3 + 18 = 17 + 18 = 35

**Step 3:**

So 20 – 18 ÷ 6 + 9 × 2 = 35

### Answer : D

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

8 + 4 × 6 – 8 ÷ 2 = 8 + 24 – 4

**Step 2:**

We do all addition and subtraction from left to right

8 + 24 – 4 = 28

**Step 3:**

So 8 + 4 × 6 – 8 ÷ 2 = 28

### Answer : C

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

7 – 52 ÷ 13 + 6 × 5 = 7 – 4 + 30

**Step 2:**

We do all addition and subtraction from left to right

7 – 4 + 30 = 3 + 30 = 33

**Step 3:**

So 7 – 52 ÷ 13 + 6 × 5 = 33

### Answer : A

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

28 ÷ 7 + 2 × 4 – 10 = 4 + 8 – 10

**Step 2:**

We do all addition and subtraction from left to right

4 + 8 – 10 = 12 – 10 = 2

**Step 3:**

So 28 ÷ 7 + 2 × 4 – 10 = 2

### Answer : A

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

15 – 6 ÷ 2 + 4 × 4 = 15 – 3 + 16

**Step 2:**

We do all addition and subtraction from left to right

15 – 3 + 16 = 12 + 16 = 28

**Step 3:**

So 15 – 6 ÷ 2 + 4 × 4 = 28

### Answer : D

### Explanation

**Step 1:**

We follow PEMDAS rule in simplifying this expression.

We do multiplication and division from left to right.

18 ÷ 6 + 3 × 7 – 11 = 3 + 21 – 11

**Step 2:**

We do all addition and subtraction from left to right

3 + 21 – 11 = 24 – 11 = 13

**Step 3:**

So 18 ÷ 6 + 3 × 7 – 11 = 13